Vertical cast-rolled heat-resistant aluminum-copper alloy and preparation method thereof
By introducing Sc and Zr elements into aluminum alloys and combining vertical casting and rolling process with homogenization heat treatment, the microstructure and process parameters were optimized, solving the problem of insufficient high-temperature performance of aluminum alloys in vertical casting and rolling process, and achieving improved high strength and heat resistance to meet the needs of high-end applications.
Patent Information
- Application Number
- CN202511004187.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-11-04
AI Technical Summary
In existing technologies, heat-resistant aluminum alloys prepared by vertical casting and rolling processes have insufficient performance at high temperatures, making it difficult to meet the needs of high-end applications such as aerospace and automotive manufacturing. Furthermore, insufficient research on microstructure and lack of process parameter optimization limit the improvement of alloy performance.
By introducing Sc and Zr elements into aluminum alloys and combining vertical casting and rolling process with homogenization heat treatment, the distribution of Sc elements was optimized, the microstructure was improved, the high-temperature stability of Al2Cu precipitate phase was enhanced, and the optimal process parameters were determined.
High-strength aluminum alloy sheets with excellent heat resistance were produced, with performance indicators reaching 200-300℃ or higher, meeting the needs of high-performance equipment and improving production efficiency and material quality.
Smart Images

Figure CN120888797A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of aluminum alloy, and particularly relates to a vertical casting-rolling heat-resistant aluminum-copper alloy and a preparation method thereof. BACKGROUND
[0002] The heat-resistant aluminum alloy refers to an aluminum alloy structural material serving for a long time above 200 DEG C, which requires sufficient strength, fatigue resistance and creep resistance at high temperature. The heat-resistant aluminum alloy is widely applied in the fields of weapons, ships, aviation, aerospace and automobiles, and has great demand for high-performance light-weight heat-resistant aluminum alloy in key parts such as the super-high-speed aircraft nacelle and manned spacecraft protective layer. The Al-Cu alloy has excellent comprehensive performance, is widely applied in the fields of aerospace industry, automobile manufacturing industry and building industry, and is a common structural material, which plays a very important role in alloy light-weight and energy saving and emission reduction. Xiao Daihong et al. cast an aluminum-copper alloy by vacuum melting, then homogenize at 500 DEG C and hot extrude at 400 DEG C, and finally quench at 525 DEG C and age at 185 DEG C, and the test shows that the mechanical performance of the aluminum-copper alloy with 0.2% Ce is optimal, and the tensile strength of the alloy at 350 DEG C reaches 170 MPa. Scandium (Sc) is the most effective micro-alloying element enhancer of aluminum alloy, the solubility of scandium in the aluminum matrix is less than 0.35 wt.%, and a small amount of scandium element added into the aluminum alloy can effectively improve the microstructure of the aluminum alloy and comprehensively improve the strength, hardness, plasticity, thermal stability and corrosion resistance of the aluminum alloy. A small amount of scandium added into the aluminum alloy can not only significantly refine the aluminum alloy grains and inhibit the recrystallization of the alloy, but also significantly improve the strength, plasticity, high-temperature performance, corrosion resistance and welding performance of the alloy, and even can enhance the anti-neutron irradiation damage performance. The researchers of Xi'an Jiaotong University select the common Al-Cu alloy and combine the micro-alloying effect of Sc element, realize the high-concentration segregation of Sc atoms at the grain boundary of Al2Cu strengthening phase particles, significantly inhibit the coarsening and growth of the particles at high temperature, and the alloy has super-ordinary high-temperature creep resistance and can safely serve for more than 350 h under the harsh creep environment of 300 DEG C and more than 30 MPa additional stress.
[0003] The vertical double-roller casting is an advanced metal processing technology, which mainly combines casting and rolling processes, realizes the solidification and plastic deformation of the metal melt in a short time, and thus produces metal plates with excellent performance. The technology combines the casting and rolling processes, realizes the rapid solidification of the high-temperature aluminum melt after contacting the roller, and directly manufactures the aluminum alloy plate by the deformation of the roller, which not only reduces the burning loss of waste aluminum remelting and the loss of plate cutting, but also improves the production efficiency and product yield, and has the following advantages:
[0004] (1) Casting nozzle manufacturing and installation
[0005] The nozzle design of the vertical casting mill can withstand a large static pressure of molten aluminum and has a special flow structure. The structure of the internal flow block in the nozzle can ensure the uniformity of the flow and temperature of the molten aluminum, and although the production and installation are complex, it can effectively ensure the stability of production.
[0006] (2) Adjustability of the nozzle
[0007] The nozzle support of the vertical casting mill can be adjusted horizontally, vertically, and obliquely to adapt to the convexity and edge difference requirements of the cast rolling plate. This adjustability makes the nozzle adjustment during production more flexible, while other casting mills lack this oblique adjustment function of the nozzle.
[0008] (3) Commonality of the nozzle and product adjustability
[0009] The vertical casting mill has good nozzle commonality, allowing for replacement of the nozzle without stopping production and online adjustment of the plate width according to demand. This not only reduces production costs, but also reduces labor intensity and prolongs the service life of the nozzle.
[0010] (4) Geometric properties of the cast rolling product
[0011] Due to the adjustability of the nozzle, the vertical casting mill has strong precision when adjusting the plate shape, especially in controlling the edge difference. In addition to traditional roll gap adjustment, it can also be quickly and easily optimized through oblique adjustment of the nozzle.
[0012] (5) Surface cleanliness
[0013] The aluminum plate exit direction of the vertical casting mill is at a 90-degree angle to the horizontal, which makes it less likely for external impurities to remain on the surface of the aluminum plate. Combined with natural bending, air blowing and cleaning systems, and roll cleaning methods, the surface cleanliness of the plate is higher than that of other casting mills.
[0014] (6) Material purity
[0015] The molten aluminum flows in the vertical casting mill with vertical static pressure, which can minimize the entry of heavy impurities into the aluminum plate and ensure the purity of the aluminum plate.
[0016] (7) Grain size uniformity
[0017] Due to the structural characteristics of the vertical casting mill, the grain size of the aluminum plate product on the upper and lower surfaces is very uniform, avoiding the common problem of grain size difference between the upper and lower surfaces on horizontal or inclined casting mills, which helps to achieve uniform deformation and product quality in the subsequent rolling process.
[0018] Horizontal twin roll casting is also a combination of casting and rolling, which makes the metal melt solidify and crystallize and plastic deformation to produce plate. Its advantage is that the equipment structure is relatively simple, the operation and maintenance are convenient, and the cost is lower in some production scenes. However, due to the influence of gravity, the flow state of the metal melt in the casting and rolling process is different from that of the vertical process, which may cause differences in the uniformity of the cast and rolled plate, affecting the performance of the alloy. Especially in the case of high requirements for microstructure uniformity, the effect may not be as good as that of vertical twin roll casting.
[0019] Spray forming process is to atomize liquid metal into small droplets and then spray and deposit on the substrate to solidify and form. It can quickly solidify, refine grains, and significantly improve the strength, hardness and thermal stability of the alloy. And in the preparation process, the composition can be flexibly controlled, and elements such as Sc can be easily added. However, the equipment of this process is complex, the cost is high, the production environment and technical personnel are demanding, and there are challenges in large-scale production, making it difficult to apply on a large scale.
[0020] Powder metallurgy process is to first make alloy raw materials into powder, and then get alloy materials through processes such as pressing and sintering. It can accurately control the composition, effectively avoid composition segregation, and make Sc elements uniformly distributed, greatly improving the performance of the alloy. At the same time, it can prepare complex-shaped parts. However, the powder preparation and processing process requires strict requirements, is easy to introduce impurities, affects the quality of the alloy, and the process steps are complicated, with low production efficiency.
[0021] However, the existing technology for preparing heat-resistant aluminum alloy by vertical casting and rolling process still has the following technical problems:
[0022] 1. Alloy performance limitations: As a key structural material serving above 200℃, the existing traditional heat-resistant aluminum alloy cannot meet the needs of high-performance equipment. For example, although Al-Cu alloy is widely used and plays an important role in aerospace, automobile manufacturing and construction industry, its performance has obvious shortcomings when facing the use of key parts such as super-high-speed aircraft nacelle and manned spacecraft protective layer, and it is difficult to meet the strict requirements of high-performance indicators such as high-temperature strength and stability.
[0023] 2. Lack of microstructure research: In the field of research on the relationship between aluminum alloy microstructure and performance, there is a significant gap. At present, there is a lack of in-depth research on the characteristics of the solidification structure of vertical casting and rolling process and its genetic effect on the high-temperature performance of the alloy, and the influence mechanism of the distribution characteristics of Sc element on the high-temperature stability of Al2Cu precipitates has not been systematically studied. This lack of microstructure research limits the further development of aluminum alloy materials science and lacks strong theoretical support for optimizing the performance of heat-resistant aluminum alloy.
[0024] 3. Process needs to be optimized: Although the vertical double-roller casting technology is an advanced metal processing technology, the existing technology lacks in process parameter optimization. When aluminum-copper alloy with Sc and Zr addition is used to prepare heat-resistant aluminum alloy by vertical casting process, the optimal alloy composition ratio, casting temperature, pressure and other key process parameters have not been determined, making it difficult to form an efficient and generalizable process technology solution. This limits the performance improvement of aluminum alloy sheets prepared by this process and fails to fully utilize the advantages of this process, resulting in problems such as low production efficiency and high product cost.
[0025] In summary, how to optimize the composition of heat-resistant aluminum alloy raw materials combined with the improvement of vertical casting process to comprehensively improve the strength, hardness, plasticity, thermal stability and corrosion resistance of the material is a technical problem to be solved by the present application. SUMMARY
[0026] In order to overcome the shortcomings of the prior art, the present application provides a room temperature gas sensor based on the principle of magnetic field enhancement. The present application introduces Sc and Zr into the alloy raw material, and combines vertical casting process and subsequent homogenization heat treatment to optimize the distribution of Sc element and improve the high temperature stability of Al2Cu precipitated phase, thereby further comprehensively improving the strength, hardness, plasticity, thermal stability and corrosion resistance of the material.
[0027] In order to achieve the above-mentioned purpose, the technical solution adopted by the present application is:
[0028] The first aspect of the present application provides a preparation method of vertical casting heat-resistant aluminum-copper alloy, which comprises the following steps:
[0029] (1) preparing 2.4% Cu, 0.2% Zr, 0.4% Sc and the balance of Al as raw materials for aluminum-copper alloy by mass percentage;
[0030] (2) melting the aluminum-copper alloy raw materials and rolling them into aluminum alloy sheets by vertical casting process;
[0031] (3) homogenizing heat treatment of the aluminum alloy sheet after cooling to obtain a heat-resistant aluminum-copper alloy.
[0032] Preferably, in step (2), the melting temperature is 680℃.
[0033] Preferably, in step (2), the casting temperature in the vertical casting process is 560℃.
[0034] Preferably, in step (2), the casting pressure in the vertical casting process is 90MPa.
[0035] Preferably, in step (3), the homogenization heat treatment refers to heat treatment at 500℃ for 8 hours.
[0036] The second aspect of the present application provides a heat-resistant aluminum-copper alloy prepared by the above preparation method.
[0037] Compared with the prior art, the present application has the following beneficial effects:
[0038] The present application optimizes the vertical double-roller casting forming process and raw material composition to prepare a new heat-resistant aluminum alloy plate with high strength and good heat resistance, which meets the expected design requirements. The performance indicators are as follows:
[0039] (1) The present application adds Zr and Sc elements to the Al-Cu alloy, especially the micro-alloying effect of Sc. Through this innovative design, the microstructure of the aluminum alloy is improved, and the strength, hardness, plasticity, thermal stability and corrosion resistance of the material are comprehensively improved. It is expected to break through the performance limitations of traditional heat-resistant aluminum alloys, and the temperature limit can reach more than 200-300℃, meeting the demand of high-performance equipment.
[0040] (2) The present application deeply explores the influence of the vertical casting process and the genetic characteristics of the solidification structure on the high-temperature performance of the alloy, as well as the influence of the distribution characteristics of Sc element on the high-temperature stability of Al2Cu precipitated phase. It is proved that the raw material composition combined with the vertical casting process and the homogenization heat treatment used in the present application can optimize the distribution of Sc element, and further improve the high-temperature stability of Al2Cu precipitated phase, thereby comprehensively improving the strength, hardness, plasticity, thermal stability and corrosion resistance of the material.
[0041] (3) The present application determines the best vertical casting process parameters, such as alloy composition ratio, casting temperature, pressure, etc., to form a set of process technology solutions that can be popularized. Through process optimization, the grain size of the plate prepared by vertical casting process is small, and the performance is excellent. It has important value for improving the production quality and efficiency of aluminum alloy materials, realizes cost reduction and efficiency improvement, expands the application of aluminum alloy in many fields, and helps to replace titanium with aluminum and steel with aluminum, and improves energy utilization efficiency. BRIEF DESCRIPTION OF DRAWINGS
[0042] Figure 1 The metallographic image of the as-cast sample in Comparative Example 1 at position S=0, wherein the left side is 50x, the middle is 100x, and the right side is 200x;
[0043] Figure 2 The metallographic image of the as-cast sample in Comparative Example 1 at position S=0.25, wherein the left side is 50x, the middle is 100x, and the right side is 200x;
[0044] Figure 3Metallographic photograph of the as-cast sample in Comparative Example 1 at position S = 0.5, in which the left side is 50x, the middle is lOOx, and the right side is 200x;
[0045] Figure 4 Metallographic photograph of the homogenized sample in Example 1 at position S = 0, in which the left side is 50x, the middle is lOOx, and the right side is 200x;
[0046] Figure 5 Metallographic photograph of the homogenized sample in Example 1 at position S = 0.25, in which the left side is 50x, the middle is lOOx, and the right side is 200x;
[0047] Figure 6 Metallographic photograph of the homogenized sample in Example 1 at position S = 0.5, in which the left side is 50x, the middle is lOOx, and the right side is 200x;
[0048] Figure 7 HV-S diagram of the homogenized sample in Example 1 and the as-cast sample in Comparative Example 1;
[0049] Figure 8 SEM point scanning diagram of different area segregation defects of the homogenized sample in Example 1 and the as-cast sample in Comparative Example 1, in which a1 is the SEM point scanning diagram of the as-cast sample at position S = 0, a2 is the SEM point scanning diagram of the as-cast sample at position S = 0.25, a3 is the SEM point scanning diagram of the as-cast sample at position S = 0.5, b1 is the SEM point scanning diagram of the homogenized sample at position S = 0, b2 is the SEM point scanning diagram of the homogenized sample at position S = 0.25, and b3 is the SEM point scanning diagram of the homogenized sample at position S = 0.5.
[0050] Figure 9 Surface scanning diagram of the center area segregation defect of the as-cast sample in Comparative Example 1, in which the upper left side is a micrograph of the segregation defect, the upper middle side is a surface scanning diagram of the segregation defect, the upper right side is a surface scanning diagram of the Al element, the lower left side is a surface scanning diagram of the Sc element, the lower middle side is a surface scanning diagram of the Cu element, and the lower right side is a surface scanning diagram of the Zr element.
[0051] Figure 10 Surface scanning diagram of the center area segregation defect of the as-cast sample in Comparative Example 1 and EDS spectra of each point, in which the left side is a surface scanning diagram of the center area segregation defect of the as-cast sample, and the right side is an EDS spectrum of each point in the surface scanning diagram.
[0052] Figure 11 Surface scanning diagram of the center area segregation defect of the homogenized sample in Example 1, in which the upper left side is a micrograph of the segregation defect, the upper middle side is a surface scanning diagram of the segregation defect, the upper right side is a surface scanning diagram of the Al element, the lower left side is a surface scanning diagram of the Sc element, the lower middle side is a surface scanning diagram of the Cu element, and the lower right side is a surface scanning diagram of the Zr element.
[0053] Figure 12 The scanning diagram of the center area segregation defect of the homogenization sample in Example 1 and the EDS spectrum of each point are shown, in which the left side is the scanning diagram of the center area segregation defect of the homogenization sample and the right side is the EDS spectrum of each point in the scanning diagram.
[0054] Figure 13 The XRD spectrum of the homogenization sample in Example 1 and the as-cast sample in Comparative Example 1 is shown, in which the red A2 is the homogenization sample and the black A1 is the as-cast sample. DETAILED DESCRIPTION
[0055] The specific embodiments of the present application are further described below. It is to be understood that the description of these embodiments is intended to help understand the present application and does not constitute a limitation of the present application. In addition, the technical features involved in each of the embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0056] The experimental methods in the following examples are all conventional methods unless otherwise specified. The experimental materials used in the following examples are all commercially available unless otherwise specified.
[0057] Example 1: Preparation of a vertical cast-rolled heat-resistant aluminum-copper alloy subjected to homogenization treatment
[0058] 2.4% of Cu, 0.2% of Zr, 0.4% of Sc and the balance of Al are prepared as raw materials of the aluminum-copper alloy in terms of mass percentage; the raw materials of the aluminum-copper alloy are melted at 680°C by a melting furnace and then rolled into an aluminum alloy plate by a vertical cast-rolling process at a cast-rolling temperature of 560°C and a cast-rolling pressure of 90 MPa; the large aluminum plate is cut into several small aluminum plates of approximately equal size by a wire cutting technique, and the small aluminum plates are treated in a homogenization heat treatment furnace set at 500°C for 8 h; after cooling, the homogenized aluminum alloy plate is cut into several aluminum alloy samples by wire cutting for use as a homogenization sample.
[0059] Comparative Example 1: Preparation of a vertical cast-rolled heat-resistant aluminum-copper alloy not subjected to homogenization treatment
[0060] 2.4% of Cu, 0.2% of Zr, 0.4% of Sc and the balance of Al are prepared as raw materials of the aluminum-copper alloy in terms of mass percentage; the raw materials of the aluminum-copper alloy are melted at 680°C by a melting furnace and then rolled into an aluminum alloy plate by a vertical cast-rolling process at a cast-rolling temperature of 560°C and a cast-rolling pressure of 90 MPa; the large aluminum plate is cut into several small aluminum plates of approximately equal size by a wire cutting technique, and the small aluminum plates are cut into several aluminum alloy samples by wire cutting for use as an as-cast sample.
[0061] Experimental Example 1: Metallographic analysis
[0062] The homogenized sample in Example 1 and the as-cast sample in Comparative Example 1 were respectively ground and polished, and then one piece of each sample was etched and observed under an electron microscope to obtain the metallographic images of the alloy. The segregation of the alloy before and after homogenization heat treatment was preliminarily recorded by metallographic detection. The metallographic image of the as-cast sample in Comparative Example 1 at position S = 0 is shown in FIG. 1; the metallographic image of the as-cast sample in Comparative Example 1 at position S = 0.25 is shown in FIG. 2; the metallographic image of the as-cast sample in Comparative Example 1 at position S = 0.5 is shown in FIG. 3; the metallographic image of the homogenized sample in Example 1 at position S = 0 is shown in FIG. 4; the metallographic image of the homogenized sample in Example 1 at position S = 0.25 is shown in FIG. 5; the metallographic image of the homogenized sample in Example 1 at position S = 0.5 is shown in FIG. 6. It can be seen from the metallographic images that the homogenization treatment effect is significant: the metallographic images at all positions (S = 0, S = 0.25, S = 0.5) show that the microstructure of the Al-2.4Cu-0.2Zr-0.4Sc alloy presents good uniformity after homogenization treatment. The obvious differences (such as grain size gradient, segregation degree difference) that may exist from the surface to the center in the original as-cast structure are significantly weakened, forming a relatively uniform equiaxed crystal structure. Figure 1 Figure 2 Figure 3 Figure 4 Figure 5 Figure 6
[0063] Experimental Example 2: Hardness Analysis
[0064] The homogenized sample in Example 1 and the as-cast sample in Comparative Example 1 were respectively ground and polished, and then one piece of each sample was etched and observed under an electron microscope to obtain the metallographic images of the alloy. The segregation of the alloy before and after homogenization heat treatment was preliminarily recorded by metallographic detection. The metallographic image of the as-cast sample in Comparative Example 1 at position S = 0 is shown in FIG. 1; the metallographic image of the as-cast sample in Comparative Example 1 at position S = 0.25 is shown in FIG. 2; the metallographic image of the as-cast sample in Comparative Example 1 at position S = 0.5 is shown in FIG. 3; the metallographic image of the homogenized sample in Example 1 at position S = 0 is shown in FIG. 4; the metallographic image of the homogenized sample in Example 1 at position S = 0.25 is shown in FIG. 5; the metallographic image of the homogenized sample in Example 1 at position S = 0.5 is shown in FIG. 6. It can be seen from the metallographic images that the homogenization treatment effect is significant: the metallographic images at all positions (S = 0, S = 0.25, S = 0.5) show that the microstructure of the Al-2.4Cu-0.2Zr-0.4Sc alloy presents good uniformity after homogenization treatment. The obvious differences (such as grain size gradient, segregation degree difference) that may exist from the surface to the center in the original as-cast structure are significantly weakened, forming a relatively uniform equiaxed crystal structure. Figure 7
[0065] Table 1
[0066]
[0067]
[0068] From the overall trend, the hardness of the two samples changes in a "U" shape from the center (0) to the edge (1) of the cross section, with the lowest hardness in the middle region (about S = 0.2-0.3) and the highest hardness at the edge (S = 0 and S = 1). Figure 7
[0069] As can be seen from the results of Table 1, for the as-cast sample, the hardness is the highest in the center region (about 58 HV), decreases towards the middle, reaches the lowest point at 2 / 5 (about 50 HV), and increases towards the edge, reaching about 61 HV at the outermost side; the hardness fluctuates greatly, indicating that the structure is non-uniform, and there is significant composition segregation or structure change. For the homogenized sample, the overall hardness level is higher than that of the as-cast sample, the minimum value is about 59 HV at the 2 / 5 position, and the maximum value (S = 0 or 1) can reach about 64 HV; the hardness curve is smoother, and the fluctuation is smaller, indicating that the structure is more uniform, and the composition distribution is improved. The hardness of the as-cast sample is non-uniform, and the hardness is higher in the center and edge regions, and the lowest in the middle region, showing the typical characteristics of as-cast structure, which may be caused by dendritic segregation or differences in cooling rate. After homogenization heat treatment, the hardness distribution is effectively improved, the hardness fluctuation is reduced, and the overall hardness level is improved, indicating that the redistribution of elements and the optimization of structure make the alloy performance more uniform and stable.
[0070] Experimental Example 3: SEM microstructure characterization, element point scanning, area scanning observation and EDS energy spectrum analysis
[0071] After grinding and polishing, one sample was taken from each of the homogenized sample in Example 1 and the as-cast sample in Comparative Example 1 for SEM microstructure characterization, element area scanning observation and EDS energy spectrum dot analysis, to detect the effect of homogenization heat treatment on the microsegregation defects of the alloy plate.
[0072] The SEM point scanning images of the segregation defects in different regions of the homogenized sample in Example 1 and the as-cast sample in Comparative Example 1 are shown in Figure 8 a1 is the SEM point scanning image of the as-cast sample in region S = 0, a2 is the SEM point scanning image of the as-cast sample in region S = 0.25, a3 is the SEM point scanning image of the as-cast sample in region S = 0.5, b1 is the SEM point scanning image of the homogenized sample in region S = 0, b2 is the SEM point scanning image of the homogenized sample in region S = 0.25, and b3 is the SEM point scanning image of the homogenized sample in region S = 0.5. As can be seen, the as-cast cast-rolled plate has serious center segregation and intergranular segregation defects, and the segregation defects are mainly distributed on the surface and 1 / 4 cross section of the cast-rolled plate, and the center region has significantly reduced segregation defects (a3 < a2 < a1). In comparison, the surface of the homogenized cast-rolled plate also has serious center segregation and intergranular segregation defects, but the defects in the 1 / 4 cross section and the center region are significantly reduced (b3 < b2 < b1), and are lower than the defects in the same regions of the as-cast sample (a1 < b1, a3 > b3), proving that the homogenization process can more effectively reduce the number and size of defects than the process parameters of the as-cast sample, and can effectively improve the mechanical properties of the plate.
[0073] To determine the composition of the center segregation band of the Al-2.4Cu-0.2Zr-0.4Sc aluminum alloy cast-rolled plate, the segregation band of the center region of the as-cast sample in Comparative Example 1 was subjected to SEM microstructure characterization and element area scanning observation, and the obtained area scanning diagram of the segregation defect of the center region of the as-cast sample in Comparative Example 1 is shown in FIG. 2, wherein the upper left side is a micrograph of the segregation defect, the upper middle is an area scanning diagram of the segregation defect, the upper right side is an area scanning diagram of the Al element, the lower left side is an area scanning diagram of the Sc element, the lower middle is an area scanning diagram of the Cu element, and the lower right side is an area scanning diagram of the Zr element. As can be seen from the results, the center segregation band defect of the alloy plate is mainly caused by the uniform distribution of Cu, Al alloying elements and trace elements Zr and Sc in the segregation region. Figure 9
[0074] To further determine the composition of the crystalline phase in the center region segregation defect of the as-cast sample in Comparative Example 1, EDS energy spectrum dot analysis was performed on the segregation region of the as-cast sample in Comparative Example 1, and the obtained scanning diagram of the center region segregation defect of the as-cast sample in Comparative Example 1 and the EDS energy spectrum diagram of each point are shown in FIG. 3, wherein the left side is a scanning diagram of the center region segregation defect of the as-cast sample, and the right side is an EDS energy spectrum diagram of each point in the scanning diagram. The EDS energy spectrum analysis results of the segregation region are shown in Table 2. Figure 10
[0075] Table 2
[0076]
[0077] As can be seen from the results in Table 2, the segregation region is mainly composed of η phase CuAl2, which is exactly the same as the area scanning analysis results.
[0078] To illustrate the effect of homogenization heat treatment on the microsegregation defect of the Al-2.4Cu-0.2Zr-0.4Sc aluminum alloy plate, the center region of the homogenization sample in Example 1 was subjected to SEM microstructure characterization, element area scanning observation and EDS energy spectrum dot analysis, and the obtained area scanning diagram of the center region segregation defect of the homogenization sample in Example 1 is shown in FIG. 4, wherein the upper left side is a micrograph of the segregation defect, the upper middle is an area scanning diagram of the segregation defect, the upper right side is an area scanning diagram of the Al element, the lower left side is an area scanning diagram of the Sc element, the lower middle is an area scanning diagram of the Cu element, and the lower right side is an area scanning diagram of the Zr element. The obtained scanning diagram of the center region segregation defect of the homogenization sample in Example 1 and the EDS energy spectrum diagram of each point are shown in FIG. 5, wherein the left side is a scanning diagram of the center region segregation defect of the as-cast sample, and the right side is an EDS energy spectrum diagram of each point in the scanning diagram. The EDS energy spectrum analysis results of the segregation region are shown in Table 3. Figure 11 Figure 12
[0079] Table 3
[0080]
[0081]
[0082] By Figure 11 、 Figure 12 The results show that the segregation area at the 1 / 2 cross-section of the center segregation band defect of the alloy plate is mainly caused by the uniform distribution of Cu, Al alloying elements and trace elements Zr and Sc in the segregation area. However, compared with the as-cast sample, the segregation area at the 1 / 2 cross-section of the homogenization sample is less and more uniform. As shown in Table 3, the segregation area at the 1 / 2 cross-section of the homogenization sample is composed of Al3(Sc, Zr) crystal phase. It is shown that the change of process parameters will not only cause the change of segregation area in different cross-sections, but also cause the change of crystal phase in the segregation area.
[0083] Example 4: XRD test
[0084] After grinding and polishing, one sample of the homogenization sample in Example 1 and the as-cast sample in Comparative Example 1 was taken for further analysis of the crystal structure of the alloy before and after homogenization heat treatment by XRD image. The XRD patterns of the homogenization sample in Example 1 and the as-cast sample in Comparative Example 1 are shown in Figure 13 , wherein the red A2 is the homogenization sample and the black A1 is the as-cast sample. The red curve (homogenization sample) and the black curve (as-cast sample) both show multiple obvious diffraction peaks with similar positions, indicating that the two samples have similar crystal structures.
[0085] As can be clearly seen from the annotation of the diffraction peaks, both the as-cast sample and the homogenization sample contain Al and CuAl2 crystal phases, and the characteristic peaks of CuAl2 are less and weaker, indicating that it is a minor phase or less distributed.
[0086] It is shown that the main crystal structure in the sample is the face-centered cubic structure of α-Al, which is the most common main phase in aluminum alloy. Since the characteristic peaks of CuAl2 appear in the XRD image (especially at about 20°-50° of 2θ), it indicates that the reaction of Cu and Al occurs in the alloy to form CuAl2 compound. This phase usually helps to improve the hardness and strength of the alloy. It is shown that there may be differences in sample preparation or heat treatment process (such as grain size, texture direction, etc.), but the phase compositions are the same. The diffraction peaks of A2 are generally stronger, indicating that the grains are coarser or the crystal orientation is more concentrated.
[0087] The embodiments of the present application are described in detail above, but the present application is not limited to the described embodiments. For those skilled in the art, various changes, modifications, replacements and variations of the embodiments can be made without departing from the principles and spirits of the present application, and still fall within the protection scope of the present application.
Claims
1. A method for preparing a vertically cast and rolled heat-resistant aluminum-copper alloy, characterized in that, The preparation method includes the following steps: (1) Prepare 2.4% Cu, 0.2% Zr, 0.4% Sc and the balance Al by mass percentage as raw materials for aluminum-copper alloy; (2) The raw materials of aluminum-copper alloy are melted and rolled into aluminum alloy plates using a vertical casting and rolling process; (3) After the aluminum alloy plate is cooled, it undergoes homogenization heat treatment to obtain a heat-resistant aluminum-copper alloy.
2. The method for preparing a vertically cast and rolled heat-resistant aluminum-copper alloy according to claim 1, characterized in that, In step (2), the melting temperature is 680°C.
3. The method for preparing a vertically cast and rolled heat-resistant aluminum-copper alloy according to claim 1, characterized in that, In step (2), the casting temperature in the vertical casting and rolling process is 560℃.
4. The method for preparing a vertically cast and rolled heat-resistant aluminum-copper alloy according to claim 1, characterized in that, In step (2), the casting pressure in the vertical casting and rolling process is 90 MPa.
5. The method for preparing a vertically cast and rolled heat-resistant aluminum-copper alloy according to claim 1, characterized in that, In step (3), the homogenization heat treatment refers to heat treatment at 500°C for 8 hours.
6. A heat-resistant aluminum-copper alloy prepared by the preparation method according to any one of claims 1-5.